Preparation and Properties of An Insensitive Booster Explosive Based on LLM‐105. Issue 1 (27th November 2012) - Xu, Wenzheng; An, Chongwei; Wang, Jingyu; Dong, Jun; Geng, Xiaoheng
Abstract A new insensitive booster explosive based on 2, 6‐diamino‐3, 5‐dinitropyrazing‐1‐oxide (LLM‐105) was prepared by a solvent‐slurry process with ethylene propylene diene monomer (EPDM) as binder. SEM (scanning electron microscopy) was employed to characterize the morphology and particle size of LLM‐105 and molding powder. The mechanical sensitivity, thermal sensitivity, shock wave sensitivity, and detonation velocity of the LLM‐105/EPDM booster were also measured and analyzed. The results show that both mechanical sensitivity and thermal sensitivity of LLM‐105/EPDM are much lower than that of conventional boosters, such as PBXN‐5 and A5. Its shock wave sensitivity is also lower than that of PBXN‐5 and PBXN‐7. When the density of charge is 95 % TMD, its theoretical and measured detonation velocities are 7858 m s−1 and 7640 m s−1, respectively. These combined properties suggested that LLM‐105/EPDM can be used as an insensitive booster.